The Activity of Active Compounds of Papaya Leaf (Carica Papaya L.) in Inhibiting the Growth of Fungus Candida Albicans in the Oral Cavity - Ana Medawati; Ika Andriani; Atiek Driana Rahmawati; Nanik Hidayati (Formosa Journal of Sustainable Research, 2023)
Candida albicans is the most frequently isolated candida species from the oral cavity. The overgrowth of C. albicans can cause opportunistic infections in the oral cavity, called oral candidiasis. On the other hand, papaya leaves (Carica papaya L.) have benefits and are efficacious as antifungal drugs. The results of various studies reveal that papaya leaves (Carica papaya L.) contain various active compounds, such as flavonoids, alkaloids, saponins, and tannins, which can inhibit the growth of C. albicans fungus. This literature review, therefore, aims to ascertain the activity of active compounds in papaya leaves in inhibiting the growth of C. albicans in the oral cavity